2015
DOI: 10.5455/ijmsph.2015.05052015254
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and use of protective eye devices among auto mechanic technicians and auto spare parts traders in Uyo, Nigeria

Abstract: are not without job-related hazards. It is, thus, necessary to apply safety rules and regulations. Their training is usually apprenticed based, lasting between 1 and 3 years. Most the auto mechanic shops are owned by a single individual, and they are generally not careful about protective devices. The few owned by big companies are located in Federal Capital and other commercial cities in Nigeria. In Uyo, the state capital of Akwa-Ibom, the local authority has carved out a section of the town called "Mechanic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Also, the association between level of education and use of protective measure revealed that low-level education is a contributory factor to non-use of protective equipment among vulcanizers in the study area. This finding supported previous findings that finding that low education level may contribute to non-use personal protective measures among small scale business workers, as they do not know, recognize and appreciate the significance of personal protective equipment (Ahmad et al, 2017;Kumar et al, 2013;Abraham et al, 2015;Taha 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Also, the association between level of education and use of protective measure revealed that low-level education is a contributory factor to non-use of protective equipment among vulcanizers in the study area. This finding supported previous findings that finding that low education level may contribute to non-use personal protective measures among small scale business workers, as they do not know, recognize and appreciate the significance of personal protective equipment (Ahmad et al, 2017;Kumar et al, 2013;Abraham et al, 2015;Taha 2000).…”
Section: Discussionsupporting
confidence: 90%
“…This finding is lower than the results from the study among welders in Zambia (98%), Nepal (90.7%), India (83.3%), and Northern Nigeria (77.9%). [ 5 16 18 19 ] Use of at least one PPE at work is found to be 44.3%, which is higher than the study among automobile workers from Ghana (27%) and Nigeria (12.8%) and is lower than the study among welders from India (95.7%)[ 10 19 20 ]. However, this finding is consistent with the study among welders in eastern Nepal.…”
Section: Discussionmentioning
confidence: 87%
“…This finding is supported by the study from Zambia. [ 18 ] In contrast to this, findings from different setting[ 5 6 20 ] have showed education is not significant with PPE use. Workers who had prior training to work were twice more likely to use PPE compared to those who did not receive any training prior to work in automobiles.…”
Section: Discussionmentioning
confidence: 94%
“…Welding protection practices refer to the measures taken to safeguard the eye against potential health hazards that may arise from exposure to welding. This objective is accomplished through the utilization of personal safety glasses, which serve as a protective barrier for the eye ( 19 ).…”
Section: Introductionmentioning
confidence: 99%